The Three Pillars of Communication in Local Culture: Driving Force in Combating Village Fund Corruption - Setiawan, Koesworo (Universitas Djuanda Bogor, 2026)
Corruption in villages continues to rise, along with the increased value of government budget assistance. Statistics on budget misuse in villages show no improvement despite ongoing law enforcement action. This article aims to identify and explain the strengths of local culture that can help overcome irregularities in village fund management. This research uses a qualitative-argumentative approach, with a literature study. Data were obtained from scientific articles and other documents relevant to the research objectives using Publish or Perish software. Data was reduced, categorized, and interpreted based on three operational concepts of the communication model in local culture: communicator (traditional figure), message (ancestral teachings), and medium (traditional institutions). Data validity was tested using two techniques: source triangulation (comparing data across relevant articles) and assuming the data in each article were valid because they had been reviewed before publication. The results show that, first, traditional figures serve as moral and ethical references. Second, teachings as messages instill values of goodness and harmony among humans, and between humans and their environment. Third, the sanction mechanism for norm violators serves as a deterrent and maintains harmony. Result reveal that, the combination of these three cultural pillars can strengthen efforts to address corruption in villages.